Assessing the Spatial Distribution of Public Toilets in Lokoja Metropolis, Kogi State, Nigeria, Mitigating Open Defecation - Johnson, N. G.; Agada, D. U.; John-Nwagwu, H. O.; Aremu, R.; Guma, E. P. (Journal of Spatial Information Sciences, 2024)
Open defecation remains a pressing public health and environmental challenge, particularly within urban centers like Lokoja Metropolis. This paper assessed the spatial distribution of public toilets as a viable solution to combat open defecation in the Lokoja metropolis using Euclidean distance measurement and Nearest Neighbor Analysis (NNA). Through a comprehensive review of existing literature and spatial analysis, this study investigates the current status of the existing public toilets, their accessibility, and their impact on open defecation practices. Furthermore, the paper explores the socio-economic factors influencing the availability and usage of public toilets. The findings suggested about twenty-four (24) locations of public toilets which are strategic distribution of public toilets and can significantly mitigate open defecation within the Lokoja metropolis. This research provides valuable insights for policymakers, urban planners, and sanitation authorities to implement targeted interventions and achieve sustainable sanitation goals within urban areas. The study recommended that the government, non-governmental organizations, and communities should provide initiatives to provide adequate public toilets at strategic locations as shown in this study as well as homes, and school environments (in hostels and school premises). The study further recommended that there should be Public awareness as regards the locations and usage of these public toilets within the metropolis.
Keywords: spatial distribution; open defecation; metropolis; public convenience; health; interventions